Health enhancing physical activity - Oja, Pekka; Borms, Jan (Perspectives the multidisciplinary series of physical education and sport science, 2004)
The book is designed to be an overall presentation of health enhancing physical activity (HEPA) Its purpose is to provide most recent theoretical and practical evidence base for HEPA experts and actors in research, education, administration and service provision.